Dynamic residual pattern of azoxystrobin in Swiss chard with contribution to safety evaluation. (15th October 2017) - Farha, Waziha; Abd El‐Aty, A. M.; Rahman, Md. Musfiqur; Kabir, Md. Humayun; Chung, Hyung Suk; Lee, Han Sol; Jeon, Jong‐Sup; Wang, Jing; Chang, Byung‐Joon; Shin, Ho‐Chul; Shim, Jae‐Han
Abstract: This study aimed at quantifying the residual amount of azoxystrobin in Swiss chard samples grown under greenhouse conditions at two different locations (Gwangju and Naju, Republic of Korea). Samples were extracted with acetonitrile, separated by salting out, and subjected to purification by using solid‐phase extraction. The analyte was identified using liquid chromatography–ultraviolet detection. The linearity of the calibration range was excellent with coefficient of determination 1.00. Recovery at three different spiking levels (0.1, 0.5, and 4 mg/kg) ranged between 82.89 and 109.46% with relative standard deviation <3. The limit of quantification, 0.01 mg/kg, was considerably much lower than the maximum residue limit (50 mg/kg) set by the Korean Ministry of Food and Drug Safety. The developed methodology was successfully used for field‐treated leaves, which were collected randomly at 0–14 days following azoxystrobin application. The rate of disappearance in/on Swiss chard was ascribed to first‐order kinetics with a half‐life of 8 and 5 days, in leaves grown in Gwangju and Naju greenhouses, respectively. Risk assessments revealed that the acceptable daily intake percentage is substantially below the risk level of consumption at day 0 (in both areas), thus encouraging its safe consumption.